Pseudogenes in Human Cancer - Poliseno, Laura; Marranci, Andrea; Pandolfi, Pier Paolo (Frontiers in Medicine, 2015)
Recent advances in the analysis of RNA-sequencing (RNA-seq) data have shown that pseudogenes are highly specific markers of cell identity and can be used as diagnostic and prognostic markers. Furthermore, genetically engineered mouse models have recently provided compelling support for a causal link between altered pseudogene expression and cancer. In this review, we discuss the most recent milestones reached in the pseudogene field and the use of pseudogenes as cancer classifiers.